(untitled) (Web of Teachers: Inderscience Research, 2025)
The article details the importance of using interactive methods in the lesson process and their types. In particular, the Brainstorming method and its importance in organizing physics lectures on the topic of material point dynamics are presented. Among these methods, the "Brainstorming" method can be used in all lessons. This method is a collection of free opinions and judgments expressed by students on a particular problem, through which a certain solution is reached. To apply the brainstorming method to the topic "Dynamics of a Material Point": first of all, such stages as studying the topic, collecting ideas, classifying ideas, and selecting the best ones can be used. It is stated that these stages contribute to a deeper understanding of the basic concepts and fundamental laws of the material point and its dynamics.